Cross-basin comparisons of water use, water scarcity and their impact on livelihoods: present and future - Harrington, Larry W.; Cook, Simon E.; Lemoalle, Jacques; Kirby, Mac; Taylor, C.; Woolley, Jonathan N. (Informa UK Limited, 2009)
We compare water availability, water use, water productivity and poverty across the diverse river basins studied by the CGIAR Challenge Program on Water and Food. Water productivity tends to be higher in drier areas and where livestock grazing is integrated with rainfed crop production. We find that links among water, food security and poverty are best understood within a historical perspective. We identify opportunities to reduce poverty through water-related interventions. The way in which waterrelated investments affect poverty is influenced by changes in demography, climate, and rural society. In most basins, these trends involve trade-offs that require good governance at local, regional and basin scales.